Review of Some Methods for Improving Transient Response in Automotive Diesel Engines through Various Turbocharging Configurations - Giakoumis, Evangelos G. (Frontiers in Mechanical Engineering, 2016)
Turbocharged diesel engines suffer from worse transient performance than their naturally aspirated counterparts, mostly at low loads and speeds. This leads to overshoot in engine-out exhaust emissions (primarily particulate matter/soot and NOx) after a speed or load increase, as well as poor drivability. The main cause for this problematic behavior is located in the turbocharger in the form of high moment of inertia and unfavorable aerodynamic-type compressor flow characteristics. In the present work, various alternative turbocharging configurations are reviewed that have proven successful in improving the dynamic diesel engine operation. These configurations are combined supercharging, variable-geometry turbine, electrically assisted turbocharging, two-stage series and sequential turbocharging, and lower turbine moment of inertia. Significant improvement in the engine’s transient response can be realized when designing for smaller turbocharger frames or applying more than one units (in series or parallel arrangement). Increasing the available turbine torque (e.g., through elevated turbine back pressure in a variable-geometry turbine) is another successful option, as well as enhancement of the boost pressure (e.g., through the use of a positive displacement compressor upstream of the turbocharger). Finally, the use of external energy (e.g., in the form of electrical assistance on the turbocharger shaft during the critical turbocharger-lag phase) is another recently developed and highly promising measure to mitigate the drawbacks of the poor transient performance of turbocharged diesel-engined vehicles and limit their exhaust emissions. The choice of the “best” configuration for a specific application depends on many parameters, such as cost, matching procedure, control system, and mainly type of engine and drive cycle of the vehicle.